ANALYSIS OF PORTALLNEWS.ID BRANDING COMMUNICATION IN BUILDING A BRAND IMAGE - Apriyanti, Sela; Pienrasmi, Hanindyalaila; Poyo, M. Denu (Journal of Public Relations and Digital Communication (JPRDC), 2023)
In running a company, a good image or brand is needed so that consumers use the company's services and products. Branding communication is one way for companies to influence consumers to use the company's products or services, even though news portal companies are no exception. The focus of this research is how the new online news portal company builds a good brand or corporate image so that it can be known by the public, especially in Bandar Lampung. The approach in this study uses a qualitative descriptive approach to produce depth on how to build a brand image on an online news portal that has not been formed for a long time. as well as conducting observations, and documentation. The results of this study describe how the portalnews.id company tries to brand their online news portal where the results are in accordance with the basis of this research to build company branding, where the four things are Research, Action Plan, Communication, and Evaluation.